Changes in physicochemical characteristics and organic acids during ripening or five tropical accepted fruit species in Malaysia - Seri Intan Mokhtar; Nur Ain Abd Aziz (Penerbit UTM Press, 2015)
Malaysia is a tropical country which is rich in various kinds of local fruits. Each has unique characteristics that could be explored further. Some of their compositions can play on important role in improving human life. The research aimed to evaluate the physicochemical composition and organic acid in 5 types of local fruit species in Malaysia, namely Averrhoa bilimbi, Eleiodoxa conferta, Mangifera indica, Phyllanthus acidus and Bouea oppositifolia at different maturity stages. It was observed that titratable acidity signiﬁcantly decreased with the increasing maturity, while total soluble solid content and pH increased with maturity. All the local fruit species at the ripe stage have higher total soluble solid content compared to young stage. Oxalic acid and ascorbic acid were present at all maturity stages of five local fruit species. Tartaric acid was only present in Bouea oppositifolia while malic acid was present in all local fruit species except for Mangifera indica.